PENERAPAN MODEL KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 07 SUNGAI TAWAR KECAMATAN KOTO XI TARUSAN - Yarna Yarna (IICET (Indonesian Institute for Counseling, Education and Therapy), 2016)
Social science learning in grade IV SDN 07 Sungai Tawar Kecamatan Koto XI Tarusan indicated some problems causing the lack of students’ learning achievement. Cooperative learning model of jigsaw lets students help each other in small group in learning process. This model includes learning runnning cooperatively between students in order to reach the learning purpose. This research was aimed to improve learning achievement of social science subject of students grade IV SDN 07 Sungai Tawar Kecamatan Koto XI Tarusan by implementing cooperative learning model of jigsaw. This research consists of two cycles. Data of research were obtained from observation and test. Researcher decided the standard of students’ successfulness as 65 and research is considered to be successful if numbers of students reaching the standard are greater than 80% of all students. After cycle I, students’ mean score is 68.70 which the percentage of successful students is 65.22%. After cycle II, students’ mean score is 75.22 which the percentage of successful students is 95.65%. Thus, it can be concluded that cooperative learning model of jigsaw can improve learning achievement of social science subject of students grade IV SDN 07 Sungai Tawar Kecamatan Koto XI Tarusan.